Socialist Structural Gaps: A Simultaneous Inference Analysis - Grubaugh, Stephen G.; Stollar, Andrew J.; Thompson, G. Rodney (The Review of Economics and Statistics, 1989)
Stephen G. Grubaugh, Andrew J. Stollar, G. Rodney Thompson, Socialist Structural Gaps: A Simultaneous Inference Analysis, The Review of Economics and Statistics, Vol. 71, No. 4 (Nov., 1989), pp. 693-698